CODE MIXING ANALYSIS IN THE ANGRY COMMUNITY ON TWITTER - Nuha Fathinah Al Fani (Universitas PGRI Palembang, 2025)
This research seeks to explore the phenomenon, types, and underlying reasons for the use of two languages (code mixing) within the